Early mortality in patients with cancer and COVID-19 infection treated with immunotherapy - Jacques Raphael; Britney Le; Simron Singh; Phillip Blanchette; Maureen Trudeau; Melody Lam; Matthew Cheung (BMC Cancer)
Abstract Background Immunotherapy in the presence of COVID-19 infections raises concerns because of potential overlapping clinical complications and immune system enhancement. Further investigation is warranted to establish its safety and to improve clinical decisions. Methods We conducted a retrospective cohort study using linked health administrative data from Ontario, Canada to assess 30-day mortality in patients with solid tumors who were treated with immunotherapy within 120 days before testing positive for COVID-19. A stepwise multivariable logistic regression model was used to identify clinical factors associated with 30-day mortality. Results Between January 2020 and April 2023, 281 patients tested positive for COVID-19 and were included in our study. The mean age was 68 (Standard Deviation: 10.3), 45% (127/281) were females and 58% (163/281) had lung cancer. 59% of patients (167/281) were treated with single agent immunotherapy, and almost 80% received at least one dose of COVID-19 vaccine. The 30-day mortality was 22% (63/281) and < 5% of patients were admitted to ICU or required ventilation. Factors associated with higher mortality were older age (Odds Ratio (OR) 1.60, 95% confidence interval (CI) 1.07–2.39), prior radiation therapy (OR 2.38, 95%CI 1.08–5.28), lower hemoglobin (< 10 g/dl) (OR 4.08, 95%CI 1.89–8.82) and higher leucocytes count (> 11,000/mm3) (OR 3.63, 95%CI 1.55–8.52). Conclusions Immunotherapy does not seem to increase the risk of 30-day mortality in patients with COVID-19 infections compared to published outcomes of patients with cancer and COVID-19. Mortality was associated with certain clinical characteristics that need to be carefully examined when prescribing immunotherapy during future comparable pandemics.